2018
DOI: 10.1262/jrd.2017-139
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between bovine endometrial thickness and plasma progesterone and estradiol concentrations in natural and induced estrus

Abstract: The objective of this study was to investigate cyclical changes in endometrial thickness in relation to progesterone (P4) and estradiol-17β (E2) concentrations during natural and induced estrus in 15 cows. In the prostaglandin (PG) F2α-induced estrus group, ultrasonography (USG) at 6-h intervals was used to determine endometrial thickness 48–24 h before the PGF2α treatment until 24 h after ovulation (ovulation = Day 0). In the natural estrus group, USG was performed every 48 h from Day 3 to Days 15–18 after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 44 publications
(72 reference statements)
1
24
1
Order By: Relevance
“…Any potential differences in timing or magnitude of the increase in EA are likely to be explained by differences in ultrasound quality and experimental model. A recent study compared the endometrial changes under natural and induced proestrus and reported a more rapid increase in endometrium size in the induced than in the natural proestrus [29]. Our results appeared to be more similar to the natural proestrus, with a gradual and constant increase in the size of the endometrium during a 48 h period rather than the rapid increase followed by a plateau that has been reported during an induced proestrus [13,29].…”
Section: Discussionsupporting
confidence: 73%
“…Any potential differences in timing or magnitude of the increase in EA are likely to be explained by differences in ultrasound quality and experimental model. A recent study compared the endometrial changes under natural and induced proestrus and reported a more rapid increase in endometrium size in the induced than in the natural proestrus [29]. Our results appeared to be more similar to the natural proestrus, with a gradual and constant increase in the size of the endometrium during a 48 h period rather than the rapid increase followed by a plateau that has been reported during an induced proestrus [13,29].…”
Section: Discussionsupporting
confidence: 73%
“…Results from these studies highly contribute to the knowledge of the endometrial transcriptomic profile at the time when an embryo is transferred into a recipient. However, they also demonstrate that the endometrial transcriptome is affected by many factors, including parity (heifers or cows), breeds (dualpurpose, beef or dairy breed), and induction of estrus 17 .…”
Section: Discussionmentioning
confidence: 98%
“…During diestrus, the endometrial stroma is thickened and uterine glands enlarged, resulting in an increased production of histotroph 14,15 that is absorbed by the trophoblast of the potential embryo 16 . The thickness of the endometrium depends on the concentration of circulating estradiol and progesterone, and it has been shown to vary between natural or induced estrous 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovulation is an important factor for the incidence of COD, and endometritis is associated with failure of ovulation (Opsomer et al, 2000;Sheldon et al, 2002). Escherichia coli is one of the major pathogens of endometritis in dairy cattle (Sheldon et al, 2002;Williams et al, 2005;Westermann et al, 2010;Sun et al, 2011). Uterine infection by E. coli increased lipopolysaccharides (LPS) in ovarian follicles (Herath et al, 2007), which causes dysfunction of the ovulation mechanism and responsiveness for steroid hormone (Polat et al, 2015).…”
Section: Discussionmentioning
confidence: 99%